Meningkatan Hasil Belajar Pendidikan Agama Katolik dan Budi Pekerti pada Materi Gereja sebagai Komunitas Umat Beriman menggunakan Model Problem Based and Learning Berbantuan Media Audio Visual di Fase D Kelas VIII SMP Negeri 1 Tanah Pinem Tahun Pelajaran - Emma Rospita Br embiring; Yusmanto Yusmanto; Busri Busri (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Learning is not just about gaining knowledge; it's about growing, evolving, and making a difference. Teachers should design lessons that help students develop both skills and knowledge, leading to the development of strong moral character. Effective learning puts students at the center of the process, making learning active, creative, and engaging. However, at SMP Negeri 1 Tanah Pinem, especially in Catholic Religious Education and Ethics, teaching is still very teacher-centered, and only 61% of students are meeting the learning objectives. To address this, the school has implemented a student-centered approach, including Problem-Based Learning (PBL). After using PBL for two cycles, it was found that while only 16% of students showed improvement in the first cycle, all students met the objectives in the second cycle. This shows that PBL has significantly improved student learning outcomes.